If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -42 = 7(8 + -1x) -42 = (8 * 7 + -1x * 7) -42 = (56 + -7x) Solving -42 = 56 + -7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7x' to each side of the equation. -42 + 7x = 56 + -7x + 7x Combine like terms: -7x + 7x = 0 -42 + 7x = 56 + 0 -42 + 7x = 56 Add '42' to each side of the equation. -42 + 42 + 7x = 56 + 42 Combine like terms: -42 + 42 = 0 0 + 7x = 56 + 42 7x = 56 + 42 Combine like terms: 56 + 42 = 98 7x = 98 Divide each side by '7'. x = 14 Simplifying x = 14
| (3x-5)+(6x-40)=90 | | (3x-5)+(6x-40)= | | -7x+10=10-7x | | 4a^2-17a-15=0 | | -5y^2+8y+7=0 | | 45/6b+4111/140=4/5b-22/5+11/7 | | 8x(9x)= | | x=(x+40) | | =2+2sin(i) | | 3(2m-1)+9=6(1m+1) | | 12+9g=93 | | =2+2sinx | | -8(x+8)= | | 6(x-4)=40 | | -2a+13/5=24/5-14/5a | | 4.2p+17=3.2p+2 | | 4x^2-13x-116=0 | | -9.2=y+7.7 | | 13.75=0.25+0.50 | | 21.6+4.4t=5.32 | | 5x(-4x+4)=1 | | 18+9p12p-31= | | -13=2.7x-1.35x | | 16.331+m=38.478 | | 9g-47g-3= | | 24577=x-76x | | f(x)=8ln(x) | | 4x+2(7x+11)=112 | | 2b-6b+3= | | 13y-22y=12 | | 1000-1= | | (3+1/3)*(2+1/2)=x |